Correlation Analysis between Dietary Intake of Tyrosols and Their Food Sources and Urinary Excretion of Tyrosol and Hydroxytyrosol in a European Population - Enrique Almanza-Aguilera; Estefanía Davila-Cordova; Daniel Guiñón-Fort; Marta Farràs; Giovanna Masala; Maria Santucci de Magistris; Ivan Baldassari; Rosario Tumino; Lisa Padroni; Verena A Katzke; Matthias B. Schulze; Augustin Scalbert; et al. (Antioxidants, 2023)
This study analyzed the correlations between the acute and habitual intake of dietary tyrosols, their main food sources, and 24 h urine excretions of tyrosol (Tyr) and hydroxytyrosol (OHTyr) in participants from the European Prospective Investigation into Cancer and Nutrition study (EPIC). Participants (n = 419) were healthy men and women aged from 34 to 73 years from 8 EPIC centers belonging to France, Italy, and Germany. Acute and habitual dietary data were collected using a standardized 24 h dietary recall software and validated country-specific dietary questionnaires, respectively. The intake of 13 dietary tyrosols was estimated using the Phenol-Explorer database. Excretions of Tyr and OHTyr in a single 24 h urine sample were analyzed using tandem mass spectrometry. Urinary excretions of Tyr, OHTyr, and their sum (Tyr + OHTyr) correlated more strongly with their corresponding acute (rhopartial~0.63) rather than habitual intakes (rhopartial~0.47). In addition, individual and combined urinary excretions of Tyr and OHTyr were weakly to moderately correlated with the acute and habitual intake of other individual tyrosol precursors (rhopartial = 0.10–0.44) and especially with major food sources, such as wine (rhopartial = 0.41–0.58), olive oil (rhopartial = 0.25–0.44), and beer (rhopartial = 0.14–0.23). Urinary Tyr + OHTyr excretions were similarly correlated with the acute intake of total tyrosols but differently correlated with food sources among countries. Based on these results, we conclude that 24 h urinary excretions of Tyr + OHTyr could be proposed as biomarkers of total tyrosol intake, preferably for acute intakes.